2013
DOI: 10.1111/bph.12285
|View full text |Cite
|
Sign up to set email alerts
|

Systemic and cerebral exposure to and pharmacokinetics of flavonols and terpene lactones after dosing standardized Ginkgo biloba leaf extracts to rats via different routes of administration

Abstract: Background and Purpose Flavonols and terpene lactones are putatively responsible for the properties of Ginkgo biloba leaf extracts that relate to prevention and treatment of cardiovascular disease and cerebral insufficiency. Here, we characterized rat systemic and cerebral exposure to these ginkgo compounds after dosing, as well as the compounds’ pharmacokinetics. Experimental Approach Rats received single or multiple doses of ShuXueNing injection (prepared from GBE50 for intravenous administration) or GBE50 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 51 publications
3
72
0
Order By: Relevance
“…After oral administration of GBTs, terpene lactones were eliminated faster than flavonols. This is consistent with Chen et al (2013). Moreover, the flavonols presented double peaks in curves of mean plasma concentration.…”
Section: Pharmacokinetics Studiessupporting
confidence: 87%
“…After oral administration of GBTs, terpene lactones were eliminated faster than flavonols. This is consistent with Chen et al (2013). Moreover, the flavonols presented double peaks in curves of mean plasma concentration.…”
Section: Pharmacokinetics Studiessupporting
confidence: 87%
“…An herbal constituent can be defined as drug-like if it possesses the desired pharmacologic potency, a wide safety margin, appropriate pharmacokinetic (PK) properties, and adequate content in the medicine dosed. Recent multicompound PK studies have indicated that human subjects and laboratory animals are considerably exposed to only a few constituents of an herbal medicine after dosing (Lu et al, 2008;Liu et al, 2009;Li et al, 2012a;Chen et al, 2013;Cheng et al, 2013;Hu et al, 2013;Jiang et al, 2015;Li et al, 2015). Such PK studies provide information for pharmacologists regarding which herbal compounds merit further evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…The observed PK interspecies difference should be considered in pharmacological research of DanHong injection. In PK studies of other herbal medicines, significant differences in elimination half-life have also been found to cause considerably different systemic exposure to herbal compounds; long elimination half-life may considerably counterbalance influence of poor oral bioavailability on systemic exposure to an herbal compound Chen et al, 2013;Jiang et al, 2015). With rapidly increasing application of analytical techniques, such as liquid chromatography/mass spectrometry, in research on herbal medicines, content levels of compounds in herbal formulations and their elimination half-lives have become more and more available in literature; such data of herbal compounds could be used together as potential PK marker to predict their systemic exposure after dosing herbal injections.…”
Section: Discussionmentioning
confidence: 99%
“…Rats were given filtered tap water and commercial rat chow ad libitum and allowed to acclimate to the facilities and environment for 3 days before use. Rats received in-house femoralartery-cannulation for blood sampling or bile duct cannulation for bile sampling (Chen et al, 2013;Cheng et al, 2013). After surgery, rats were housed individually and allowed to regain their preoperative body weights before further use.…”
Section: Methodsmentioning
confidence: 99%